Micropropagação de Calendula officinalis L - Bertoni, B. W.; Damião Filho, C. F. [UNESP]; Moro, J. R. [UNESP]; França, S. C.; Pereira, A. M S (My University, 2006)
Micropropagation of Calendula officinalis L. is usually propagated through seeds and therefore shows high diversity in flower size and colour, what causes quantitative and qualitative chemical variability. A micropropagation protocol was established for clonal propagation of this species to achieve homogeneous biomass, more appropriate for the production of phytotherapics. Explants harvested from capitula were the most appropriate for the micropropagation process. MS culture medium supplemented with 1.0 mgL-1 BAP and 6.0 gL-1 Phytagel™ enhanced shoot proliferation, while MS medium supplemented with 0.5 mgL-1 Kinetin and 6.0 gL-1 Phytagel™, increased shoot elongation. Plantlets (80%) cultured in MS/2 medium supplemented with 1.0 mgL-1 de IBA rooted.
Micropropagation of Calendula officinalis L
Keywords: Calêndula; Medicinal plant; Micropropagation; kinetin; biomass; clonal variation; controlled study; culture medium; flower; harvesting; marigold; micropropagation; Murashige and Skoog medium; nonhuman; phytotherapy; plant root; plant seed; shoot growth; species cultivation; Calendula; Calendula officinalis